A new varanopid synapsid from the early Permian of Oklahoma and the evolutionary stasis in this clade. Issue 10 (23rd October 2019) - Maho, Sigi; Gee, Bryan M.; Reisz, Robert R.
Abstract : Varanopids are a basal clade of small- to medium-sized non-therapsid synapsids, whose range extends from the late Pennsylvanian to the late middle Permian, and are found in North America, Russia, Europe and South Africa. The greatest varanopid diversity is observed at the fossiliferous cave deposits near Richards Spur, Oklahoma, well known for the preservation of a complex early Permian upland community. Two previously described varanopids, Mycterosaurus and Varanops, are known only from fragmentary disarticulated material at Richards Spur. A third putative varanopid, Basicranodon fortsillensis, represented by a partial parasphenoid, has been synonymized with Mycterosaurus longiceps . This study reports on a new varanopid taxon, represented by substantially more complete material, including three nearly complete skulls. Such comprehensive cranial material allows for a detailed study of the taxon and its relationship to other varanopids. This new varanopid bears great morphological similarity to Mesenosaurus romeri from the middle Permian Mezen River Basin of northern Russia. Phylogenetic analysis recovers a sister relationship between this taxon and Me. romeri . This relationship, in conjunction with a detailed morphological comparison, supports the placement of this taxon within Mesenosaurus, as a new species, Me. efremovi . These results reveal an unexpected extension of the geographical and temporal range of Mesenosaurus, contributing to our understanding of varanopid dispersal. The extended persistence of this basal clade of predatory synapsids, underscored by the apparent evolutionary stasis of this genus, is unusual among Palaeozoic tetrapods. This phenomenon implies an exceptionally high degree of extended ecological resilience across major faunal and environmental transitions.